Evaluation of noninvasive monitoring of brain oxygenation during surgical treatment of hypoplastic aortic arch with antegrade cerebral perfusion in neonates and infants - A. Petrenko; Y. Truba; S. Boyko; L. Prokopovych; M. Teslar; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2016)
The present work represents the results of monitoring of the brain oxygenation and other parameters (perfusion pressure, pulse oximetry, thermometry, lactate levels, blood gas analyses) of 9 children with hypoplasia of all segments of the aortic arch with coarctation of the aorta and concomitant intracardiac pathologies during surgical treatment with antegrade cerebral perfusion.